Ride quality comparison of a quarter car model with a nonlinear hydraulic damper and an andre hartford friction damper - Ridhuan Siradj , Fadly Jashi Darsivan; Shahimi, Sharis Shazzali (Global Illuminators, 2014)
The paper discusses the ride quality of two different quarter car models. Attached to the first model is a nonlinear passive hydraulic damper while the second model is equiped with an Andre Hartford friction damper. Both of the dampers are physically tested and their characteristics are obtained by using a damper test rig. Based on the force-velocity curves of the dampers polynomial models are developed through the implementation of Lavenberg-Marquadt algorithm. Once the coefficients of the polynomials for both dampers are obtained the equations are plugged into the quarter car model and by using Scilab the response of the system are simulated using a 4th order Runge-Kutta algorithm. The disturbance to the system is assumed of having a step and a sinusoidal inputs. Based on these disturbances the vertical displacements and vertical accelerations of the sprung mass for both systems are analyzed. From the results obtained the ride quality of both systems are determined by the magnitudes of the accelerations and the settling time of the sprung mass. The smaller the acceleration and the faster the system settles indicate that the ride quality of the system is better than the other.